Competing Private Ports : Lessons from Argentina - Estache, Antonio (World Bank, Washington, DC, 2012)
Port reforms in Argentina have sought to deregulate, decentralize, and privatize. And they have sought to introduce competition not only among ports but also for the ports --by inviting operators to bid for port concessions-- and within the ports-- by dividing large ports into terminals and offering each as a separate concession. Bidders were asked to set their own charges, subject to a maximum price cap for cargo, and concessions were awarded on the basis of the highest rental offered for the infrastructure and equipment. The results have been generally positive, with increased productivity, higher cargo volumes, and big reductions in tariffs. The authors look at the lessons from the reform and set out the remaining challenges.